A little life eaudiobook A novel. - Yanagihara, Hanya (Books on Tape, 2022)
NEW YORK TIMES BESTSELLER • A stunning “portrait of the enduring grace of friendship” ( NPR ) about the families we are born into, and those that we make for ourselves. A masterful depiction of love in the twenty-first century. NATIONAL BOOK AWARD FINALIST • MAN BOOKER PRIZE FINALIST • WINNER OF THE KIRKUS PRIZE A Little Life follows four college classmates—broke, adrift, and buoyed only by their friendship and ambition—as they move to New York in search of fame and fortune. While their relationships, which are tinged by addiction, success, and pride, deepen over the decades, the men are held together by their devotion to the brilliant, enigmatic Jude, a man scarred by an unspeakable childhood trauma. A hymn to brotherly bonds and a masterful depiction of love in the twenty-first century, Hanya Yanagihara’s stunning novel is about the families we are born into, and those that we make for ourselves. Look for Hanya Yanagihara’s latest bestselling novel, To Paradise.